Purification and characterization of a new xylanase (APX-II) from the fungus Aureobasidium pullulans Y-2311-1. - Li, X L (1993)
Aureobasidium pullulans Y-2311-1 produced four major xylanases (EC 3.2.1.8) with pI values of 4.0, 7.3, 7.9, and 9.4 as revealed by isoelectric focusing and zymogram analysis when grown for 4 days on 1.0% oat spelt xylan. The enzyme with a pI of 9.4 was purified by ammonium sulfate precipitation, chromatography on a DEAE-Sephadex A-50 column, and gel filtration with a Sephadex G-75 column. The enzyme had a mass of about 25 kDa as determined by both sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel filtration chromatography. The purified enzyme had a Km of 7.6 mg . ml(-1) and Vmax of 2,650 micromol . min(-1) . mg(-1) for birchwood xylan at 28 degrees C and pH 4.5. It lacked activity towards carboxymethylcellulose, cellobiose, starch, mannan, p-nitrophenyl (pNP)-beta-D-xylopyranoside, pNP-beta-D-glucopyranoside, pNP-alpha-D-glucopyranoside, pNP-beta-D-cellobioside, pNP-beta-D-fucopyranoside, or pNP-alpha-D-galactopyranoside. The predominant end products of birchwood xylan or xylohexaose hydrolysis were xylobiose and xylose. The enzyme had the highest activity of pH 4.8 and 54 degrees C. Sixty percent of the activity remained after the enzyme had been incubated at 55 degrees C and pH 4.5 for 30 min. The sequence of the first 68 amino acid residues at the amino terminus showed homology to those of several other xylonases. Immunoblot analysis with antiserum raised against the purified xylanase revealed that two immunologically related polypeptides of 25 and 22 kDa were produced in A. pullulans cultures containing oat spelt xylan or xylose as carbon sources but not in cultures containing glycerol or glucose.